2000
DOI: 10.1046/j.1365-2648.2000.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on vulnerability using emic and etic approaches

Abstract: New perspectives on vulnerability using emic and etic approaches The concept of vulnerability has not been developed theoretically from a nursing perspective. It has been viewed epidemiologically as population-based relative risk with little consideration of its experiential qualities. The purpose of this paper is to analyse critically the use of the term vulnerability using elements of concept clarification and a critical literature review. A new perspective of vulnerability is offered based on differentiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0
16

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 21 publications
3
160
0
16
Order By: Relevance
“…Spiers (2000) demonstrated that the term vulnerability needs to be viewed from etic and emic perspectives. Spiers (2000) reported that attributes of the etic perspective of vulnerability include endangerment, functional capacity, external recognition, measurable behaviour, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Spiers (2000) demonstrated that the term vulnerability needs to be viewed from etic and emic perspectives. Spiers (2000) reported that attributes of the etic perspective of vulnerability include endangerment, functional capacity, external recognition, measurable behaviour, etc.…”
Section: Discussionmentioning
confidence: 99%
“…One important challenge has been to the exclusive prerogative of professionals to identify vulnerability in respect of suspected 'adults at risk'. This sits uneasily both with a social model of disability and with understandings of vulnerability as a subjective experience (Spiers, 2000). One practical, micro-level implication is that people's own views must be heard, not merely when deciding how to respond to vulnerability and harm, but also when deciding whether and in what sense to consider a person vulnerable at all (Dunn et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, they reject being categorised as vulnerable and/or in need of protection, because they associate this with deficit, paternalism and stigma (Brown, 2011). This in turn connects with arguments that vulnerability has a significant subjective component (Spiers, 2000), and that people's own views of themselves and their situations are therefore relevant to its definition (Dunn et al, 2008).…”
Section: Vulnerability In Policy Law and Practicementioning
confidence: 99%
“…There is a distinctive literature on household energy vulnerability, understood as a set of circumstances that underpin the risk of falling into fuel and energy poverty. Having applied Spiers (2000) understanding of 'emic' vulnerability to utility services such as heating and cooling, Middlemiss and Gillard (2015) suggest that energy vulnerability can also be articulated via a bottom-up perspective that characterizes experiences of deprivation.…”
Section: Revisiting the 'New Energy Paradigm' Via A Geographical Lensmentioning
confidence: 99%